Kepatuhan Perawatan pada Pasien Diabetes Mellitus Tipe 2 - I Made Mertha; I Made Widastra; I Gusti Ayu Ketut Purnamawati (Jurnal Gema Keperawatan, 2014)
This study aimed to identity treatment adherence in patients with Diabetes Mellitus Type 2in Interna Policlinic at Negara General Hospital. This was a quantitative descriftive study with crossectional subject-approach model. This study use the non probability sampling with 30 sample. Sampling technicque with consecutive sampling technique that use questionnaires treatment adherence. The results obtained is 14 respondents (46,7%) treatment adherence and 4 respondents (13,3%) not treatment adherence.